If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = c + -2 Reorder the terms: 4 = -2 + c Solving 4 = -2 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 4 + -1c = -2 + c + -1c Combine like terms: c + -1c = 0 4 + -1c = -2 + 0 4 + -1c = -2 Add '-4' to each side of the equation. 4 + -4 + -1c = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -1c = -2 + -4 -1c = -2 + -4 Combine like terms: -2 + -4 = -6 -1c = -6 Divide each side by '-1'. c = 6 Simplifying c = 6
| 7y=5x-1 | | 97=2.1p+27.7 | | 4x-2(-2)=10 | | 9xsquared+11x-14=0 | | 9.75km=m | | 7y=2-5x | | m+20=12 | | y=-1+0.8x | | 17=15y-3 | | 2x=9x+5 | | 6x+4=2(18-x) | | 9w+9=9w+9 | | 5y=4x-5 | | 4d-3=d+9 | | 6-3c=c+8 | | 3(2x+1)=5(x+3) | | (14x-13)(5x+13)=70X^2+182 | | 8-3b=4-2b | | 8k^2+10k+3=0 | | 2(10-3x)=8 | | 10x=1.8x+32 | | 8k+10k+3=0 | | 2(2x+8)=0 | | 0=2x^2-7 | | 12+m/6=18 | | 3z+1=-11 | | -45d^7+48d^6+45d^5=0 | | 20-n=-3 | | g+11=7 | | -m^4-7m^3-12m^2=0 | | 5+3a+5a^2-7x-3a-2a^2= | | x^2+5y+4y^2=0 |